Sinergi dan Kerjasama Dalam Pengembangan Coal Bed Methane (CBM) dan Langkah Kebijakan Investasi dan Lingkungan Hidup - Hasibuan, Afriadi Sjahbana (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2016)
Coal-Bed Methane or CBM as an alternative energy source has been the attention of many people. The interest in CBM it can be a renewable energy due to the gas continue to be produced during the coal seam is still there. Moreover, Indonesia has a large CBM reserves of 450 TCF (trillion cubic feet) that can meet the needs of Indonesia for almost 300 years if the terms of the current natural gas consumption. Therefore, the development of CBM in Indonesia is very important to maintain energy security and optimize the use of natural resource in Indonesia. Therefore, the development of CBM in Indonesia is very important to maintain energy security and optimize the use of natural resources in Indonesia. This study provides insight on: (1) The synergies and cooperation among stakeholders to realize the develoment of CBM good efficient and effective. (2) Innovation policy in order to increase the attractiveness for companies to invest CBM is based on sustainable environtment development. (3) Improve regional economic growth that spreads to surrounding areas. If the three aspects of running consistently which will have an impact on improving the preosperity of society, energy sufficiency and improve intelligence Indonesian nation in the future